Hubungan Celebrity Endorser dengan Keputusan Pembelian Halosnap.Id di Media Sosial Instagram - Adinda Sabilla; Mohamad Subur Drajat (Jurnal Riset Public Relations, 2023)
ABSTRACT : There is a significant relationship between credibility (X1) in Nizaramrullah's video reels and the Halosnap.Id (Y) Purchase Decision with the strength of the relationship being in the moderate category with a positive value. There is a significant relationship between attractiveness (X2) in the video reels viewing regarding Halosnap's purchasing decisions .Id(Y) with the strength of the relationship is in the moderate category with positive value. There is a significant relationship between power (X3) in the video reels viewing regarding the purchase decision of Halosnap.Id(Y) with the strength of the relationship in the moderate category with positive valueABSTRAK : Terdapat hubungan yang signifikan antara credibility (X1) dalam tayangan video reels Nizaramrullah dengan Keputusan Pembelian Halosnap.Id (Y) dengan kekuatan hubungan berada dalam kategori moderate bernilai positif. Terdapat hubungan yang signifikan antara attractiveness (X2) dalam tayangan video reels mengenai keputusan pembelian Halosnap.Id(Y) dengan kekuatan hubungan berada dalam kategori moderate bernilai positif Terdapat hubungan yang signifikan antara power (X3) dalam tayangan video reels mengenai keputusan pembelian Halosnap.Id(Y) dengan kekuatan hubungan berada dalam kategori moderate bernilai positif.